2020
DOI: 10.2174/1874331502014010198
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality and Antibiotics' Susceptibility Profile of Small-medium Scale Commercial Fish farms in Nigeria

Abstract: Background: Fish currently provide 6.7% of all proteins consumed by humans globally; nevertheless, the aquaculture system has been linked to fish, environmental contamination and disease outbreak. The aim of this study was to determine the bacteriological quality and the antibiotic resistance profile of bacteria from water samples of pond stocked with Tilapia and Catfish in Ile-Ife, Osun State, Nigeria. Objective: To isolate, identify and characterise heterotrophic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Resistance was also observed to cefixime (80%), gentamicin (73.3%) and nitrofurantoin (66.7%). The study further reported that 16.6% and 8.3% of the isolates were resistant to ciprofloxacin and ofloxacin, respectively [ 102 ]. Another study in catfish farms in Nigeria reported that out of the 20 Salmonella hadar isolates, 2 (10%) were resistant to neomycin, 1 (5%) was resistant to spectinomycin, and 9 (45%) were resistant to streptomycin, whereas 7 (35%) and 4 (20%) were resistant to sulfamethoxazole and trimethoprim, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance was also observed to cefixime (80%), gentamicin (73.3%) and nitrofurantoin (66.7%). The study further reported that 16.6% and 8.3% of the isolates were resistant to ciprofloxacin and ofloxacin, respectively [ 102 ]. Another study in catfish farms in Nigeria reported that out of the 20 Salmonella hadar isolates, 2 (10%) were resistant to neomycin, 1 (5%) was resistant to spectinomycin, and 9 (45%) were resistant to streptomycin, whereas 7 (35%) and 4 (20%) were resistant to sulfamethoxazole and trimethoprim, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Associated to this, many farmers do not observe the withdrawal periods. In the study conducted by Fakorede et al [53], fish pond was reported as a reservoir of multi-drug resistant bacteria. The authors also mentioned that fish pond could serve as environmental source of drug resistance gene transfer.…”
Section: Antibiotic Resistance Profile Of Strains Isolated From Braised Products Sold the City Of Bangangtementioning
confidence: 99%
“…The results of this study suggest that the commonly used antibiotics in the city of Bangangte will not be effective for the management of diseases associated with consumption of braised fish and chicken products. Microbial multidrug resistance of pathogens isolated from ready-to-eat braised fish and chicken products sold in the city of Bangangte therefore frustrates efforts for disease control resulting in a prolonged hospitalization of patients [53].…”
Section: Antibiotic Resistance Profile Of Strains Isolated From Braised Products Sold the City Of Bangangtementioning
confidence: 99%
“…One of the world's industries with the quickest rate of growth is aquaculture and in Nigeria, aquaculture fish production had experienced a tremendous increase in recent years [4]. A balanced diet should include seafood because it is nutrient-rich and has a number of positive health effects, thereby leading to increase in the demand for these food products [5].…”
Section: Introductionmentioning
confidence: 99%
“…This hereby makes the consumption of the contaminated fish detrimental to human health [13]. Additionally, contamination of aquaculture systems has been reported to be due to poor water quality caused by pollution of water bodies due to urbanization [14], large number of fish in the system, contaminated feeds and the use of untreated animal manure [4]. Ondo State is said to be the highest producer of fish in South-West Nigeria [5].…”
Section: Introductionmentioning
confidence: 99%